1995
DOI: 10.1177/019262339502300401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Hepatocellular Proliferating Cell Nuclear Antigen Labeling Indices and Growth Fractions, p34cdc2 Kinases, and Serum Enzymes in Carbon Tetrachloride-Treated Rats

Abstract: We evaluated various biomarkers associated with cell proliferation immediately following insult with the classic hepatotoxicant carbon tetrachloride (CCl 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Monticello et al (1995) demonstrated that a single necrogenic dose of CCl 4 at 120 mg/kg increases a plasma level of ALT from 59 to 2,492 IU/l and percent of hepatocytes in S phase from 1% to 20%. The difference in necrotic and proliferative potentials between CCl 4 and DMF can be seen in absence of both the GST-P-positive foci found in the present study and the altered hepatocellular foci following 13-week inhalation exposure of rats to DMF vapor (Senoh et al, 2003), whereas 13-week inhalation exposure to CCl 4 vapor induced both the GST-P-positive hepatocellular foci and the acidophilic, basophilic and clear altered cell foci (Nagano et al, 2007a).…”
Section: Note2mentioning
confidence: 99%
“…Monticello et al (1995) demonstrated that a single necrogenic dose of CCl 4 at 120 mg/kg increases a plasma level of ALT from 59 to 2,492 IU/l and percent of hepatocytes in S phase from 1% to 20%. The difference in necrotic and proliferative potentials between CCl 4 and DMF can be seen in absence of both the GST-P-positive foci found in the present study and the altered hepatocellular foci following 13-week inhalation exposure of rats to DMF vapor (Senoh et al, 2003), whereas 13-week inhalation exposure to CCl 4 vapor induced both the GST-P-positive hepatocellular foci and the acidophilic, basophilic and clear altered cell foci (Nagano et al, 2007a).…”
Section: Note2mentioning
confidence: 99%
“…Further, recent studies indicate a PCNA interaction with proteins involved in cell cycle progression, which are not a part of the DNA polymerase apparatus but directly affect the DNA synthesis (2). PCNA expression is widely used as a marker of proliferating cells detected by immunocytochemistry (3,4) and by ELISA (4,5). A set of monoclonal antibodies are commercially available for both immunocytochemical detection of PCNA in paraffin-embedded tissue sections or cryostat sections and the identification of the protein by immunoblotting.…”
mentioning
confidence: 99%
“…The DNA amplification strategy has been designated the combined chain reaction (CCR) 1 because it combines polymerase chain reaction (PCR) (2, 3) and ligase chain reaction (LCR) (4,5). In this report, we have applied CCR to site-directed mutagenesis (Fig.…”
mentioning
confidence: 99%